2004
DOI: 10.1080/03014223.2004.9518383
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal activity and habitat associations ofMecodema howittiandMegadromus guerinii,two endemic New Zealand ground beetles (Coleoptera: Carabidae)

Abstract: Seasonal activity and habitat associations of the threatened endemic forest carabid Mecodema howitti Castelnau, and the sympatric but common endemic Megadromus guerinii (Chaudoir), were studied by pitfall trapping in a montane podocarp/hardwood forest remnant on Banks Peninsula, Canterbury, New Zealand. The main surface activity period for adult M. howitti and Mg. guerinii was the austral spring and summer. Megadromus guerinii was active across a wider temperature range than M. howitti, and was less inhibited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…oconnori from pitfall traps in winter appears to be because beetles are inactive during colder weather. Anderson et al (2004) observed a similar pattern for carabids on Banks Peninsula.…”
Section: Seasonal Activitysupporting
confidence: 60%
See 2 more Smart Citations
“…oconnori from pitfall traps in winter appears to be because beetles are inactive during colder weather. Anderson et al (2004) observed a similar pattern for carabids on Banks Peninsula.…”
Section: Seasonal Activitysupporting
confidence: 60%
“…In contrast, New Zealand has a relatively mild, maritime climate with a lack of distinct seasonality (Hurnard 1978), and New Zealand carabids were thought to display "little or no seasonality" (Watt 1978). Manual searches under surface refuges on Banks Peninsula confirmed that adult beetles were present throughout the year (Anderson et al 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three replicate 50 ha stands of 1-year-old P. radiata were sampled monthly from November 2002 to February 2003 and again in their 2nd year postharvest (mid-December to February 2004). The sampling period covered the known maximum activity periods for New Zealand carabids (Pawson and Emberson, 2001;Cartellieri and Lö vei, 2003;Anderson et al, 2004).…”
Section: Experimental Designmentioning
confidence: 99%
“…Within the late spring to summer period, activity peaks at different times for different invertebrates. For example, some beetles can be more active in spring (Anderson et al 2004), while wētā can be more active in early summer (Van Wyngaarden 1995). There is little information on how invertebrates in New Zealand respond to precipitation beyond observations of wētā activity in wet and dry conditions (Watts & Thornburrow 2009).…”
Section: Introductionmentioning
confidence: 99%